Noun-based constructions in the history of Portuguese and Spanish - Amaral, Patrícia M. 1975-; Delicado Cantero, Manuel (Oxford University Press, 2022)
"This book explores the syntactic and semantic change of three types of constructions in Spanish and Portuguese: (i) complex DPs with clausal adjunction (el hecho de, o facto de), (ii) complex prepositions/complementizers and complex connectives (sin embargo de/sem embargo de, so(b) pena de), and (iii) complex predicates containing light verbs (dar consejo/conselho de). While these constructions are syntactically different, they are all clause-taking complex expressions containing a noun followed by the functional preposition de ('of'). This book is the first work to examine them together through a systematic comparative corpus study. This makes it possible to tease apart individual from general changes and to focus on the chronological clustering of changes involving complex constructions in both languages. The development of these constructions has multiple causes related to the noun. Specifically, the reanalysis of the entire expression is affected both by the meaning of the noun and by changes in complementation patterns that systematically affected nouns (as well as verbs and adjectives) in the 16th-17th centuries in both languages. By studying mechanisms of language change and their outcomes in two sister languages, the book addresses questions like: How do complex constructions evolve? How does the meaning of the noun change when considered in isolation and when compared to the meaning of the whole construction? How do syntactic categories change over time? Studies of closely related languages, which can reveal distinct developments occurring in parallel over time, provide a crucial test case for theories of language change"--
Literaturverzeichnis Seite 169-182
Keywords: Kontrastive Syntax; Spanisch; Historische Sprachwissenschaft; Portugiesisch